Enseignant-chercheur des écoles d’architecture : unicité d’un statut, pluralité d’identités professionnelles - Rachel Metzger; Jérôme Eneau; Jacques Audran (Éducation et Socialisation)
Since 1968, architectural education in France has undergone numerous reforms, the most recent of which in 2018 created the status of ‘teacher-researcher at the Ecoles Nationales Supérieures d'Architecture (ENSA)’. Although this status applies uniformly to the disparate group of teaching staff, difficulties have been identified in developing, harmonising and stabilising this new status, particularly in view of the diversity of origins, backgrounds and ways in which ENSA teacher-researchers practise their profession. A doctoral research project currently underway examines here the question of the place of research, linked to that of the professional identities of the players who make up this new profession. Analysis of 20 interviews conducted in four ENSAs shows that these issues are closely linked to the proximity of their profile to the university model.